KEBIJAKAN HUKUM TERHADAP ASAS PERLINDUNGAN KONSUMEN PADA PRAKTIK LELANG MOBIL SECARA ONLINE - Nabilah Febriana; Zazili, Ahmad; Rohaini (Program Studi Hukum Universitas Pamulang, 2025)
Online car auctions in Indonesia are increasingly popular, but the application of distributive and retributive justice principles in this system still faces various challenges, such as information imbalance, data manipulation, and weak law enforcement. This study aims to analyze the effectiveness of the application of these two principles in protecting consumers as well as the role of personal data protection in preventing information manipulation in online auction transactions. Based on the analysis, it is found that although there are regulations governing consumer protection and personal data, the implementation of these regulations is still not optimal. Information asymmetry that occurs in online auction transactions, manipulation practices such as shill bidding, and weak supervision of auction algorithms and misuse of personal data are the main obstacles in creating justice for consumers. In addition, strengthening legal sanctions and implementing new technologies such as blockchain are needed to improve transparency and accountability in online auctions. This research also recommends the need for strengthening regulations, collaboration between the government, auction organizers, and supervisory agencies, as well as consumer education to improve legal literacy. With these measures, it is expected that the online auction system in Indonesia can become more fair, safe, and transparent, and can provide maximum protection for consumers.